Exploring cytokinesis block micronucleus assay in Croatia: A journey through the past, present, and future in biomonitoring of the general population - Gajski, Goran; Kašuba, Vilena; Milić, Mirta; Gerić, Marko; Matković, Katarina; Delić, Luka; Nikolić, Maja; Pavičić, Martina; Rozgaj, Ružica; Garaj-Vrhovac, Vera; Kopjar, Nevenka (Mutation research. Genetic toxicology and environmental mutagenesis, 2024)
In this study, we used the cytokinesis-block micronucleus (CBMN) assay to evaluate the background frequency of cytogenetic damage in peripheral blood lymphocytes of the general population concerning different anthropometric data and lifestyle factors. The background frequency of CBMN assay parameters was analysed in 850 healthy, occupationally non-exposed male and female subjects (average age, 38±11 years) gathered from the general Croatian population from 2000 to 2023. The mean background values for micronuclei (MNi) in the whole population were 5.3±4.3 per 1000 binucleated cells, while the mean frequency of nucleoplasmic bridges (NPBs) was 0.7±1.3 and of nuclear buds (NBUDs) 3.1±3.2. The cut-off value, which corresponds to the 95th percentile of the distribution of 850 individual values, was 14 MNi, 3 NPBs, and 9 NBUDs. Results from our database also showed an association of the tested genomic instability parameters with age and sex but also with other lifestyle factors. These findings underscore the importance of considering several anthropometric and lifestyle factors when conducting biomonitoring studies. Overall, the normal and cut-off values attained here present normal values for the general population that can later serve as baseline values for further human biomonitoring studies either in Croatia or worldwide. •Background frequency of micronucleus assay parameters was assessed in the general population.•Results present baseline data that could be considered normal values.•Association with age, sex, and several lifestyle factors was found.•Results can serve as baseline values for further human biomonitoring studies.